2021
DOI: 10.1021/acs.chemmater.1c00555
|View full text |Cite
|
Sign up to set email alerts
|

Material Design Strategy for Halide Solid Electrolytes Li3MX6 (X = Cl, Br, and I) for All-Solid-State High-Voltage Li-Ion Batteries

Abstract: Although several solid electrolyte (SE) candidates have been explored, achieving the necessary combination of performance, stability, and processability has been challenging. Recently, several lithium ternary halides have attracted increasing attention for SEs because of their favorable combination of high ionic conductivity and wide electrochemical window. This study aims to provide a material design strategy for lithium halides Li3MX6 (X = Cl, Br, and I) for high-voltage all-solid-state Li-ion batteries, ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
85
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(93 citation statements)
references
References 55 publications
8
85
0
Order By: Relevance
“…Furthermore, Wang et al 18 showed that introducing one and three anti-site defects between Li + and Y 3+ yields an average activation energy of 0.28±0.03 eV and 0.31±0.03 eV, respectively. Similarly, Kim et al, 71 who included 32 explicit van der Waals corrections in their AIMD simulation, obtained a larger average Li + migration activation energy of ≈0.370 eV. While the existing data is in agreement with our results of Figure 8d, by explicitly considering the occurrence of stacking faults in the LYC structure, our simulations go beyond the analysis of Li + migration in pristine bulk structures, which cannot reflect the defect-rich mechanochemically synthesized structures.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Furthermore, Wang et al 18 showed that introducing one and three anti-site defects between Li + and Y 3+ yields an average activation energy of 0.28±0.03 eV and 0.31±0.03 eV, respectively. Similarly, Kim et al, 71 who included 32 explicit van der Waals corrections in their AIMD simulation, obtained a larger average Li + migration activation energy of ≈0.370 eV. While the existing data is in agreement with our results of Figure 8d, by explicitly considering the occurrence of stacking faults in the LYC structure, our simulations go beyond the analysis of Li + migration in pristine bulk structures, which cannot reflect the defect-rich mechanochemically synthesized structures.…”
Section: Discussionsupporting
confidence: 90%
“…In general, our computed migration barriers agree well with previous computational data. 18,71 Using AIMD on a M1 -M2-bulk configuration, Wang et al 18 derived an average migration barrier of ≈0.19±0.03 eV, which is in agreement with our findings for out-of-plane diffusion. In contrast, they reported a much smaller barrier (≈0.23±0.06 eV) (all confidence intervals listed are 1σ) for the in-plane Li + migration pathway (≈0.358 eV in this work).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…[ 26 ] Halide SSEs can even be synthesized by a facile wet‐chemistry method using water as a solvent. [ 27,28 ] Furthermore, halide SSEs, especially chlorides and fluorides, exhibit wide electrochemical windows among all types of SSEs, which have been proven by theoretical [ 12,29 ] and experimental [ 30,31 ] studies. Until now, all the solid‐state batteries in the halide SSEs system are still focused on traditional oxide cathodes.…”
Section: Introductionmentioning
confidence: 99%
“…Different electrolyte 4 chemistries indeed differ in their thermodynamic stability against oxidation and reduction, in their electronic and ionic conductivity, in their softness (which is higher for halides than for argyrodite and thiophosphates) and lastly in their thermal stability. 22 Moreover, their chemical-physical properties were also shown to depend on their synthesis method, either via solvent assisted reactions involving precipitation/crystallization in organic solvents, high temperature solid-state reactions (>500 °C) or mechanical ball milling followed by annealing steps. [23][24][25][26] Among them, the solvent-based routes appear to be particularly attractive for solid electrolyte (SE) -CAM composite preparation in a core-shell like structure (namely SE-coated oxide) by maximizing the energy density at electrode level while enhancing ionic percolation and boosting the cell performance.…”
Section: Introductionmentioning
confidence: 99%